2004
DOI: 10.1080/00087114.2004.10589417
|View full text |Cite
|
Sign up to set email alerts
|

Cytological study of sixSalviaspecies (lamiaceae) from the Hengduanshan Mountains region of China

Abstract: -Salvia is a genus with surprisingly diverse chromosome numbers. In this paper six species were cytologically studied from Hengduanshan Mountains region, where is one of two diversification centers of the genus. S. przewalskii var. przewalskii is a tetraploid with the chromosome number of 2n=4x=32, other five species are the diploids with chromosome numbers of 2n=2x=16. The basic chromosome number x=8 was inferred for all species studied, which was different from x=7, 11 and 16 reported for species of the genu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Observation and analysis of meiotic process is conductive to study the morphologic and genomic variety within a species (Song and Li 2009). In this paper, we studied the behavior of chromosomes and cells in meiosis division of S. przewalskii, and the results revealed that it was a tetraploid species with the chromosomes number of 2n=4x=32 (as the basic chromosome number of the species of Salvia is eight), which was in conformity with a previous report (Yang et al 2004). Meiotic observations indicated the presence of 16 bivalents at metaphase I in most PMCs, and multivalents and univalents only appeared with rather low frequency.…”
Section: Discussionsupporting
confidence: 88%
“…Observation and analysis of meiotic process is conductive to study the morphologic and genomic variety within a species (Song and Li 2009). In this paper, we studied the behavior of chromosomes and cells in meiosis division of S. przewalskii, and the results revealed that it was a tetraploid species with the chromosomes number of 2n=4x=32 (as the basic chromosome number of the species of Salvia is eight), which was in conformity with a previous report (Yang et al 2004). Meiotic observations indicated the presence of 16 bivalents at metaphase I in most PMCs, and multivalents and univalents only appeared with rather low frequency.…”
Section: Discussionsupporting
confidence: 88%
“…taxa have 2n=12-64 chromosome numbers (Afzal-Rafii 1976, 1980, Haque and Ghoshal 1980, Haque 1981, Nakipoğlu 1993a, b, Ozdemir and Senel 1999, Tunamoto et al 2000, Alberto et al 2003, Zhiyun et al 2004, Ozkan 2006, Ozkan and Soy 2007, Yang et al 2009, Masoudi et al 2010, Zhen-Qiao et al 2010, Sheidai and Alijanpoo 2011, Martin et al 2011. Although cytological studies are abundant, karyological studies about Salvia taxa growing in Turkey are little (Martin et al 2011(Martin et al , 2015.…”
Section: Resultsmentioning
confidence: 99%
“…Centromeric index is between 29.17 μm and 45.91 μm (Table 3). Several basic chromosomes of Salvia indicate that species from the distinct areas have characterized separately after spreading (Zhiyun et al 2004). On the other hand, there were no satellites and B chromosomes observed in this study.…”
Section: Salvia Virgata Jacq 2n = 18mentioning
confidence: 99%
“…Various studies about cytological data on Salvia taxa from Europe, America, Asia and Turkey demonstrated that Salvia has several basic chromosome numbers [n = 6, 7, 8, 9, 10, 11, 12, 13, 15, 16, 18 and 32] (Afzal-Rafii 1976;Haque and Ghoshal 1980;Haque 1981;Nakipoglu 1993aNakipoglu , 1993bOzdemir and Senel 1999;Tunamoto et al 2000;Alberto et al 2003;Zhiyun et al 2004;Ozkan 2006;Ozkan and Soy 2007;Yang et al 2009;Masoudi et al 2010;Song et al 2010;Martin et al 2011;Sheidai and Alijanpoo 2011). However, there were no detailed chromosome and karyotype studies of the taxa in this study.…”
Section: Introductionmentioning
confidence: 99%